Chapter 15 Aldous Huxley and the Rebels against Happiness - Farrell, John (Taylor & Francis, 2023)
Huxley's vision of juvenile happiness kept in place by genetic engineering, compulsory promiscuity, psychological conditioning, drugs, and propaganda has been traditionally read as a warning against the dangers to modern freedom. Huxley would seem, then, to be a strong defender of the heroic protest against utopia. In fact, Huxley believed that most of the measures taken by the World State, including eugenics, would be necessary in some form, and his narrative strongly ironizes the resisters to utopian happiness. Unable to grasp either horn of the utopian dilemma, he produced a lucid and memorable version of it.